Differentiation Between Tendinous, Myotendinous and Myofascial Injuries by L-BIA in Professional Football Players - Nescolarde, Lexa; Terricabras, Joaquim; Mechó, Sandra; Rodas, Gil; Yanguas, Javier (Frontiers in Physiology, 2020)
Purpose To differentiate by localized bioimpedance (L-BIA) measurements 24 h after injury, between tendinous, myotendinous junction (MTJ), and myofascial junction (MFJ) injuries, previously diagnosed by MRI exam. To evaluate by L-BIA, the severity of MTJ injuries graded from 1 to 3, and to determine the relationship between days to return to play (RTP) and L-BIA measurements. Methods 3T MRI and tetra polar L-BIA was used to analyzed 37 muscle injuries 24 h after injury in 32 male professional football players, (23.5 ± 1.5 kg m–2; 1.8 ± 0.1 m; 20–30 year.) between the 2016–2017 and 2017–2018 seasons. Muscle injuries were classified by The British Athletics Muscle Injury Classification (BAMIC). Percentage difference of L-BIA parameters [resistance (R), reactance (Xc), and phase angle (PA)] of the injured side were calculated considering contralateral non-injured side as the reference value. Results According to BAMIC classification and by MRI exam, we found tendinous (n = 4), MTJ (n = 26), and MFJ (n = 7) muscle injuries. In addition, MTJ injuries were grouped according to the severity of injury in grade 1 (n = 11), grade 2 (n = 8), and grade 3 (n = 7). Significant decrease (P < 0.01) was found in the L-BIA parameters R, Xc, and PA, in both MTJ and MFJ as well as in the different grades of MTJ injuries. In particular, in Xc (P < 0.001), which is related to muscle cell disruption. Regarding days to RTP, there was statistical significance among the three different grades of MTJ injuries (P < 0.001), especially when grade 1 was compared to grade 3 and grade 2 compared to 3. Conclusion L-BIA is a complementary method to imaging diagnostic techniques, such as MRI and US, to quantify MTJ and MFJ injuries. In addition, the increase in the severity of the MTJ injury resulted in higher changes of the Xc parameter and longer time to RTP.